O-GlcNAcylated p53 in the liver modulates hepatic glucose production - Maria J. Gonzalez-Rellan (Nature Portfolio, 2021)
p53 regulates signalling pathways involved in metabolic homeostasis. Here the authors show that O-GlcNAcylation of p53 in the liver plays a key role in the physiological regulation of glucose homeostasis, potentially via controlling the expression of the gluconeogenic enzyme phosphoenolpyruvate carboxykinase.